025 The utility of nerve blood flow in the assessment of peripheral neuropathy. (29th July 2019) - Borire, Adeniyi; Issar, Tushar; Kwai, Natalie; Visser, Leo; Poynten, Ann; Simon, Neil; Kiernan, Matthew; Krishnan, Arun
Abstract : Introduction: Animal and human studies of diabetes have shown significant alterations in nerve blood flow (NBF), which may also play a role in the development of neuropathy. However, the non-invasive assessment of NBF in human subjects has remained elusive until the recent technological advancements in ultrasound (US) technology. We undertook sonographic assessment of NBF in 75 patients with type 2 diabetes and correlated the findings with neuropathy severity scores and electrophysiological parameters. Methods: Blinded median and tibial nerve ultrasound scans were performed at non-entrapment sites using a high-resolution linear probe. NBF was quantified using power Doppler techniques to obtain the vessel score (VSc) and maximum perfusion intensity (MPI). Routine nerve conduction studies were performed, and neuropathy severity was assessed using the total neuropathy score (TNS). Aged- and gender-matched controls were enrolled. Results: Diabetic nerves had higher rates of NBF detection (28%) compared to the control group (p<0.0001). Significant correlations were found between NBF parameters and nerve size (p<0.001), reported sensory symptoms (p<0.05) and neuropathy severity scores (p<0.001). The cohort with diabetes had significantly larger median (8.5 ± 0.3 mm 2 vs. 7.2 ± 0.1 mm 2, p<0.05) and tibial (18.0 ± 0.9 mm 2 vs. 12. 8 ±0.5 mm 2, p<0.05) nerves compared to controls. Conclusions: Peripheral nerve hypervascularity is detectable by US in moderate to severe diabetic neuropathy with prominent sensory dysfunction. Consistent with previous studies, the sonographic detection of NBF is a pathological finding.